Praktik Peradilan Pidana Terhadap Pelaku Tindak Pidana Pencurian Yang Dilakukan DalamRuang Lingkup Keluarga(Studi Kasus Di Wilayah Hukum Pengadilan Negeri Karanganyar) - Rimadana, Feitmila; , Muchammad Iksan, SH.MH; , Marisa Kurnianingsih, S.H., M.H., M.Kn (2016)
Theft within the scope of the family is to a complaint that the prosecution can only be done if there is a complaint from the victim or aggrieved. This study aims to determine the consideration of the families of the perpetrators of the theft within the scope of the family themselves were not reported to the authorities, to determine the consideration and the consequences of the Investigator Police if there are cases of theft within the family that have been lodged, but suddenly revoked by the family, and basic consideration of the judge in examining and deciding criminal case of theft committed within the scope of the family in Karanganyar District Court's Decision No. 124 / Pid.B / 2013 / PN.Kray. The research method using descriptive empirical jurisdiction. Sources of primary data, interviews and secondary data sources of primary law, secondary and tertiary. Data were collected by interview and literature study then analyzed the data qualitatively. The results showed that there are several reasons for not reporting the case to the appropriate authorities, as follows indemnify, theft perpetrators are the backbone of the family, there are family relationships, and the victim felt pity to economic circumstances the offender. Consequences of the police against the revocation of the complaint was based on the request of the victim is still a family relationship, then the police may not assign the case file to the prosecutor, so that the public prosecutor can not prosecute the case. The judge in imposing a criminal case based on juridical considerations the facts revealed at the hearing and sociological considerations in considering the aspect of a factor in terms of the severity of the punishment, as stated in the sound of Article 197 paragraph (1) f the KUHAP.